Revitalisation of cultural heritage and historical objects - Jagodič, Gregor (Mednarodno inovativno poslovanje, 2025)
Purpose of the article –this paper explores the revitalisation of historic buildings through the lens of financial sustainability, community engagement, and regional development, arguing that heritage renewal should transcend mere technical restoration.Research methodology –the study integrates an extensive review of both domestic and international literature with qualitative analyses of selected good practices. It focuses particularly on financing models, tourism integration, public-private partnerships, the role of local communities, and the contribution of digital technologies.Findings –the research highlights that the success of revitalisation projects depends primarily on diversified funding sources, strategic content development, and the creation of sustainable business models that combine public and private interests. Active communityparticipation and the use of digital tools—such as augmented and virtual reality—further enhance the appeal and long-term functionality of revitalised heritage sites.
Keywords: cultural heritage; digitalisation; digitalizacija; kulturna dediščina; revitalisation; revitalizacija; sustainable development; tourism; trajnostni razvoj; turizem